Discovery of fused tricyclic core containing HCV NS5A inhibitors with pan-genotype activity. Issue 13 (1st July 2016) - Yu, Wensheng; Coburn, Craig A.; Yang, De-Yi; Meinke, Peter T.; Wong, Michael; Rosenblum, Stuart B.; Chen, Kevin X.; Njoroge, George F.; Chen, Lei; Dwyer, Michael P.; Jiang, Yueheng; Nair, Anilkumar G.; et al.
Graphical abstract: Abstract: HCV NS5A inhibitors have demonstrated impressive in vitro potency profiles in HCV replicon assays and robust HCV RNA titer reduction in the clinic making them attractive components for inclusion in an all oral fixed dose combination regimen for the treatment of HCV infection. Herein, we describe research efforts that led to the discovery of a series of fused tricyclic core containing HCV NS5A inhibitors such as24, 39, 40, 43, and44 which have pan-genotype activity and are orally bioavailable in the rat.